2008
DOI: 10.1002/da.20426
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression and posttraumatic stress disorder in an outpatient population before and after Hurricane Katrina

Abstract: The aim of the present investigation was to evaluate symptoms of depression and posttraumatic stress disorder (PTSD) in an outpatient psychiatric population before and after Hurricane Katrina. The sample consisted of 156 patients (110 females; M(age)=41.2 years, SD=10.9) at an outpatient psychiatric clinic who completed measures of psychological symptoms as part of their regular clinical care in the month before (n=76; 49%) and the 1 month after (n=80; 51%) Hurricane Katrina made landfall. Partially consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
(20 reference statements)
2
24
0
Order By: Relevance
“…Increased rates of depression after disasters have been well-documented (Arata et al 2000; Buttke et al 2012; Carrasco et al 2007; Cerdá et al 2013; Galea et al 2002; Lyons et al 1999; McLeish and Del Ben 2008), and the results of the present study confirm these findings. Using the same metric, though not directly comparable, only ~20% of individuals in the general population would be expected to exhibit depressive symptoms (Radloff 1977).…”
Section: Discussionsupporting
confidence: 89%
“…Increased rates of depression after disasters have been well-documented (Arata et al 2000; Buttke et al 2012; Carrasco et al 2007; Cerdá et al 2013; Galea et al 2002; Lyons et al 1999; McLeish and Del Ben 2008), and the results of the present study confirm these findings. Using the same metric, though not directly comparable, only ~20% of individuals in the general population would be expected to exhibit depressive symptoms (Radloff 1977).…”
Section: Discussionsupporting
confidence: 89%
“…For example, one study of New York City residents following September 11 found that the association between reported frequency of viewed televised images and probable PTSD remained even after controlling for lifetime history of traumatic events, death of a friend or family in the September 11 attacks, and direct involvement in the rescue efforts following the attacks [19]. After controlling for various exposure factors, among other variables, McLeish and Del Ben [20] found a significant association between Hurricane Katrina television viewing and PTSD symptoms in a sample of psychiatric outpatients who were directly exposed to the disaster. After controlling for demographics and other exposures, Nishi and colleagues [6] reported a significant association between television viewing of coverage of the 2011 Great East Japan Earthquake and Tsunami and PTSD symptoms in a sample of disaster medical assistance responders deployed to the disaster site.…”
Section: Discussionmentioning
confidence: 99%
“…L. Whaley oppression Whaley, 2001). Studies reveal a positive association between viewing TV coverage of the aftermath of Katrina and PTSD symptoms (McLeish & Del Ben, 2008;Weems et al, 2007). This may be one reason for that positive correlation.…”
Section: Recognizing and Alleviating Compound Traumamentioning
confidence: 99%
“…Moreover, these studies often find stress reactions (e.g., anxiety, depression) to be more common than PTSD (McLeish & Del Ben, 2008;Najarian et al, 2001;North et al, 2008). We often think of PTSD as the most likely adverse reaction to traumatic experiences, but only about 10% to 30% of a population exposed to man-made events or natural disasters will develop such severe trauma-related illness (Dohrenwend et al, 2006;Perilla et al, 2002).…”
mentioning
confidence: 99%